Daily Dose Standardization Based on Essential and Nonessential Trace Element Presence in Berberis baluchistanica Ahrendt Bark, Leaf, and Root. (25th April 2022) - Gul, Zareen; Akbar, Ali; Leghari, Saadullah Khan; Kakar, Attiq Ur Rehman; Khan, Naqeebullah; Muhammad, Javed; Khan, Nazir Ahmad; Rehman, Zia Ur; Kamal, Rehana; Ali, Imran
Abstract : Medicinal plants have great importance to the consumer health, as beside beneficial compounds, plants can accumulate essential and nonessential metals from soil and surrounding environments, leading to consumer health risks. Assuming this, the present study is aimed at evaluating the elemental composition and daily dose standardization based on essential and nonessential trace element presence in of bark, leaves, and roots of Berberis baluchistanica Ahrendt, a common medicinal plant used as a folk medicine in the region. Atomic absorption and flame emission spectroscopy were performed to analyze the presence of essential and nonessential elements manganese (Mn), copper (Cu), lead (Pb), nickel (Ni), iron (Fe), sodium (Na), and potassium (K). Among the essential elements, K was present at high concentrations in the bark (8926.98 ± 0.32 μ g / g ), leaves (7922.77 ± 0.42 μ g / g ), and roots (6668.5 ± 0.96 μ g / g ) of the plant. The estimated concentration of Na was higher in leaves (1782.56 ± 0.13 μ g / g ), followed by roots (1089.5 ± 0.71 μ g / g ) and bark (572.8 ± 0.62 μ g / g ). The Fe concentration varied in the range of 394.7 ± 0.3 μ g / g in bark, 1298.3 ± 0.54 μ g / g in leaves, and 1208.9 ± 0.7 μ g / g in roots. The trace transition element Mn was highest in leaves (42.7 ± 0.99 μ g / g ), followed by roots (33.5 ± 0.94 μ g / g ) and bark (22 ± 1 μ g / g ). The Cu concentration was low, ranging from 20.1 ± 0.63 to 22.67 ± 0.7 μ g / g in leaves, bark, and roots. The obtained concentration of nonessential element Pb was relatively lower than the permissible range (10 mgL–1) established by the World Health Organization. The elemental concentrations in all parts were within the set limits for provisional tolerable daily maximum intake (PTDMI) and provisional tolerable weekly intake (PTWI), and the hazard quotient index (HQ) was below 1 for all toxic metals. The micro and macroelemental distribution and the overall medicinal potential of any medicinal plant can be correlated for dose risk estimation, which will be useful in providing knowledge regarding the contraindication associated with folk medicines. In the present study, based on the elemental composition, it was calculated that the daily safe dose for Berberis baluchistanica is approximately 2-5 g/day of raw powder for an adult, which must not be exceeded to this safe range.